2013
DOI: 10.1098/rsfs.2012.0065
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal architecture and activity of the human heart

Abstract: One contribution of 25 to a Theme Issue 'The virtual physiological human: integrative approaches to computational biomedicine'. We construct the components for a family of computational models of the electrophysiology of the human foetal heart from 60 days gestational age (DGA) to full term. This requires both cell excitation models that reconstruct the myocyte action potentials, and datasets of cardiac geometry and architecture. Fast lowangle shot and diffusion tensor magnetic resonance imaging (DT-MRI) of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…Previous DTI studies of developing prenatal and postnatal hearts reported different trends (13,(60)(61)(62). Human fetal studies reported progressively increasing FA and nearly no coherent fiber organization in fetal hearts taken at early points of the second trimester compared with term hearts (60,61). A pig DTI study reported increasing FA in mid-gestation hearts that decreased after birth, with clearly detectable and coherent fiber organization at all fetal and term ages (13).…”
Section: Discussionmentioning
confidence: 96%
“…Previous DTI studies of developing prenatal and postnatal hearts reported different trends (13,(60)(61)(62). Human fetal studies reported progressively increasing FA and nearly no coherent fiber organization in fetal hearts taken at early points of the second trimester compared with term hearts (60,61). A pig DTI study reported increasing FA in mid-gestation hearts that decreased after birth, with clearly detectable and coherent fiber organization at all fetal and term ages (13).…”
Section: Discussionmentioning
confidence: 96%
“…It is the combination of the longitudinal and radial orientations that provides the complete anatomical description of the orientation of the cardiomyocytes. 47 In previous investigations, the radial orientation of the cardiomyocytes has been assessed either as the intrusion angle, 8,29,39,40,48 or more often as the transverse angle 12,13,21,22,25,30,32,33,49,50 (Figures 2G and H). Both angles are assessed relative to the epicardial curvature.…”
Section: The Radial Orientationmentioning
confidence: 99%
“…Different investigators have used different reference points when assessing angles. In some studies, the only point of reference used is the left ventricular long axis, shown as e ax in our Figure A . Systolic mural thickening, however, which is the main rearrangement of the myocardium through the cardiac cycle, occurs relative to a radial axis at right angles to the epicardium, shown as e r in Figure B.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foetal ECG [6,7] was extracted from maternal recordings (non-invasive monitoring of uterine electrical activity) from a Monica AN24 via electrodes placed on the abdomen. Episodes of foetal tachycardia were initially located using Monica software, and then the raw V(t) exported for graphical analysis.…”
Section: Putative Foetal Ventricular Fibrillationmentioning
confidence: 99%